Intense Light-Mediated Circadian Cardioprotection via Transcriptional Reprogramming of the Endothelium - Oyama, Yoshimasa; Bartman, Colleen M.; Bonney, Stephanie; Lee, J. Scott; Walker, Lori A.; Han, Jun; Borchers, Christoph H.; Buttrick, Peter M.; Aherne, Carol M.; Clendenen, Nathan; Colgan, Sean P.; Eckle, Tobias (Cell reports (Cambridge), 2019)
Consistent daylight oscillations and abundant oxygen availability are fundamental to human health. Here, we investigate the intersection between light-sensing (Period 2 [PER2]) and oxygen-sensing (hypoxia-inducible factor [HIF1A]) pathways in cellular adaptation to myocardial ischemia. We demonstrate that intense light is cardioprotective via circadian PER2 amplitude enhancement, mimicking hypoxia-elicited adenosine- and HIF1A-metabolic adaptation to myocardial ischemia under normoxic conditions. Whole-genome array from intense light-exposed wild-type or Per2−/− mice and myocardial ischemia in endothelial-specific PER2-deficient mice uncover a critical role for intense light in maintaining endothelial barrier function via light-enhanced HIF1A transcription. A proteomics screen in human endothelia reveals a dominant role for PER2 in metabolic reprogramming to hypoxia via mitochondrial translocation, tricarboxylic acid (TCA) cycle enzyme activity regulation, and HIF1A transcriptional adaption to hypoxia. Translational investigation of intense light in human subjects identifies similar PER2 mechanisms, implicating the use of intense light for the treatment of cardiovascular disease. [Display omitted] •Intense light-mediated cardioprotection requires endothelial-specific PER2•Intense light-elicited PER2 transcriptionally reprograms the endothelium•Endothelial PER2 regulates respiration and barrier function during hypoxia•Studies of humans reveal intense light activates PER2-dependent metabolism Oyama et al. investigate the mechanisms that underlie intense light-mediated protection from myocardial ischemia and find that intense light increases the circadian amplitude of PER2, which preconditions the myocardium via adenosine and HIF1A transcriptional reprogramming of the endothelium before an ischemic event.